The Formation of Composite Ti-Al-N Coatings Using Filtered Vacuum Arc Deposition with Separate Cathodes; Metals; Vol. 7, iss. 11 - Shulepov I. A. Ivan Anisimovich; Kashkarov E. B. Egor Borisovich; Stepanov I. B. Igor Borisovich; Syrtanov M. S. Maksim Sergeevich; Sutygina A. N. Alina Nikolaevna; Shanenkov I. I. Ivan Igorevich; Obrosov A. Aleksey; Weifs S. Sabine (2017, 2017)
Title screen